2006
DOI: 10.1080/14767050600676273
|View full text |Cite
|
Sign up to set email alerts
|

A case of isolated peripartum elevation of alkaline phosphatase in pregnancy complicated by gestational diabetes

Abstract: Several isoenzymes of alkaline phosphatase are present in pregnancy, the most common are of liver, bone, and placental origin. We report a case of pregnancy complicated by hypertension and gestational diabetes, in which an extremely high elevation in bone isoenzyme was noted during labor. The enzyme level returned to normal by six weeks postpartum. Elevations in total serum alkaline phosphatase during pregnancy or labor cannot be assumed to arise from the placenta, and should be further investigated to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Heazell et al 2006 reported a case of pregnancy complicated by gestational diabetes and hypertension in which extremely high elevation of bone specific isoenzyme of alkaline phosphatase was noted during labour this lead to elevation in total serum alkaline phosphatase which couldn’t be assume to arise from placenta. [5354]…”
Section: Discussionmentioning
confidence: 99%
“…Heazell et al 2006 reported a case of pregnancy complicated by gestational diabetes and hypertension in which extremely high elevation of bone specific isoenzyme of alkaline phosphatase was noted during labour this lead to elevation in total serum alkaline phosphatase which couldn’t be assume to arise from placenta. [5354]…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have demonstrated a statically significant correlation between the second trimester elevation in ALPt and preterm delivery [6,7] further researches are needed to confirm these results. In the remaining two reports, increased alkaline phosphatase serum levels were originating from osteal tissue (8,9). In a recently published report [10], a 22-year-old primigravida delivered a 37þ2 weeks' stillborn baby due to placental abruption.…”
Section: Commentmentioning
confidence: 95%
“…Characterization by electrophoresis should be performed to determine the origin of ALP. Several studies suggest an association between elevated ALP activity and preeclampsia [3][4][5][6], low birth weight, prematurity and placental insufficiency [7][8][9]. We present a case report of a 38-year-old female with uncontrolled chronic hypertension and extreme elevation of ALP and its association with placental dysfunction, demonstrated by placental pathology.…”
Section: Introductionmentioning
confidence: 92%